Assessment of the Periodontal Cementum Ablation Depth during Root Planing by an Er:YAG Laser at Different Energy Densities: An Ex Vivo Study - Paul Nahas; Saad Houeis; Remi Chamboredon; Daniel Heysselaer; Toni Zeinoun; Samir Nammour (MDPI AG, 2023)
Introduction: An important and non-adapted delivered energy of Er:YAG laser can eliminate the total thickness of root cementum during root planing. Conversely, the preservation of a partial layer of cementum covering the roots is vital for any periodontal ligament regeneration. Thus, the assessment of the cementum ablation depth produced by each energy density of Er:YAG laser is essential before considering its use for the periodontal planing and treatment of the cementum and root surfaces. Aim of the study: Assessment of the cementum ablation depth at different energy densities of the Er:YAG laser is the aim of this study. Materials and methods: A total of 48 human caries free molars were collected and used in this study. Areas to be irradiated were delimited by two longitudinal grooves (0.5 mm depth). Roots were divided randomly into four groups (4 × n = 12). An Er:YAG laser (2.94 µm) was used with a side-firing tip (R600T) with a 600 µm diameter and a frequency of 20 Hz combined with a cooling system of air 6 mL/min and water 4 mL/min. We used a super short pulse mode (SSP: pulse duration: 50 μs). We used a single irradiation passage backward from apex to cervical parts at 1 mm/s with a slight contact and at an angle of 15° to 30° between the tip and the root surface. Different energies were selected: 30 mJ, 40 mJ, 50 mJ, and 60 mJ. Results: Microscopic observations showed that the average of the ablation depth increased with the increase of the delivered energy from 30 mJ to 60 mJ. Mean values of the ablation depths were respectively as follows: 43.75 ± 4.89 µm for the energy of 30 mJ, 50.05 ± 3.72 µm for 40 mJ, 65.56 ± 10.35 µm for 50 mJ, and 74.80 ± 15.23 µm for 60 mJ. A statistically significant difference existed between the ablation depth of all groups. Conclusion: Based on our results, the depth of cementum debridement is related to the level of the delivered energy. The lowest energy levels (30 mJ and 40 mJ) can ablate the root cementum surface for a variable depth from 43.75 ± 4.89 μm to 50.05 ± 3.72 μm.